SIGNING OF DEEDS CARRIED OUTSIDE THE AREA OF THE NOTARY'S OFFICE - Alfathania, Rada; Gozali, Djoni Sumardi (International Peneliti Ekonomi, Sosial dan Teknologi, 2025)
Notaries as public officials have territorially limited authority in carrying out their duties based on Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning Notary Positions (UUJN). This study examines the legal problems that arise when a notary signs a deed outside his/her area of ??office, which is a violation of the provisions on the territorial authority of a notary. This study uses a normative legal research method with a statute approach and a conceptual approach. The data used are secondary data in the form of primary, secondary, and tertiary legal materials which are analyzed qualitatively using descriptive analysis techniques. The results of the study indicate that: First, the status of a deed signed outside the notary's area of ??office experiences a degradation of evidentiary power. Based on Article 15 paragraph (1) UUJN which states that a notary is authorized to make authentic deeds regarding all acts, agreements, and determinations required by laws and/or desired by the interested party to be stated in an authentic deed, but is limited to the area of ??his/her office as regulated in Article 17 paragraph (1) letter a UUJN. Deeds made outside the area of ??his/her office lose their authenticity and only have the power of proof as a private deed. Second, the legal consequences for a notary who signs a deed outside the area of ??his/her office can be in the form of administrative, civil, and criminal sanctions. Administrative sanctions are in the form of verbal warnings, written warnings, temporary dismissal, honorable dismissal, or dishonorable dismissal as regulated in Article 17 paragraph (2) UUJN.